The Duke of Zhou and Ritual Practice in the "Jinteng" Chapter: A Comparison of the Tsinghua Slips, Shu and Shiji Versions 周公與《金縢》中的儀式實踐：以清華簡、《尚書》及《史記》為例 - Gesterkamp, Lennert (Confucian Classics and Thought 儒家典籍與思想研究, 2021)
Textual study on the Jinteng chapter preserved in three different versions: the bamboo slips version in the collection of the Tsinghua University, the Jinteng chapter in the Book of Documents, and the version in Sima Qian's Record of the Grand Scribe. The three versions are compared for their representation of ritual practice which differ subtly but significantly. Such differences not only point to different and conflicting ideologies of their authors, but also the practice of rewriting and re-editing an existing story or legend to suit the ideas and needs of the authors. Because the Duke of Zhou is credited with the invention of "Confucian" ritual as the enfeoffed Lord of the Lu state, the study further sheds new light on these claims. 《金謄》是《尚書》中的著名篇章，記錄周公禱祭祖先代替周武王生病的故事，以此解釋周公雖然没有做王，但可能在祖先那裹取得了合法的允許。除了《尚書》之外，過去我們巳知《史記》中應有《金謄》中的故事，與《尚書》大同小異。不過，最近發現的清華大學收藏的竹簡本，給我們機會重新對比《金樣》三個不同的版本。因爲祭祀的實踐在故事中占著關鍵位置，本文特別關注三個版本《金謄》中的儀式實踐和描寫，發現它們代表兩個不同且相反的儀式傳統。清華簡應該代表楚國或剔國的看法，即經過儀式和靈界的同意才能得到做王的認可和權力，《尚書》和《史記》應該代表魯國的看法，輕視儀式的重要性，而強調周家族血脈關係和周禮（指魯國），是一種輕｀｀史"重｀｀儒"的新趨勢。從戰圉 末期或秦漠的這種對立中，西周時代的周公變成兩派中的一位共同偶像，表明兩派把傳説和歷史中的周公，修改爲自己遣一派的理想人物。遺種情 況有助於我們認識到，戰國秦漢時期很可能没有一個關於周公的固定故事，雖然只有一個主題，但分別代表了不同政治觀念的人，把故事修改爲不同的理想故事，以凸顗他們各自的政治觀，卻不一定代表一種歷史事